SOURCES OF THE ENGLISH VOCABULARY.TYPES OF AND SEMANTIC PECULARITIES OF LATIN BORROWING IN ENGLISH. ("Conference on Universal Science Research 2023", 2024)
The study of foreign languagees teaches and encourages respect for other peoples: it fosters an understanding of the interrelation of language and human nature. Foreign languages expand one's view of the world, liberalize one's experiences, and make one more flexible and tolerant. A language is a structured system of communication used by humans. Languages can be based on speech and gesture, sign, or writing. The structure of language is its grammar and the free components are its vocabulary.